Tonga : 2017 Article IV Consultation-Press Release; and the Staff Report for Tonga. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that over recent years, Tonga has enjoyed robust growth and macroeconomic stability. Growth continued to be strong at 2.7 percent in FY2017 following 3.4 percent in FY2016, supported by construction, agriculture, tourism, strong remittances, and strong private credit growth. Inflation spiked in FY2017 because of a new import tax and an increase in domestic food prices. The country's external position weakened slightly owing to construction-related imports, with reserves supported by strong remittances and donor aid. The outlook for the Tongan economy is favorable, despite external headwinds. Real GDP growth is projected at 3.4 percent in FY2018, driven by construction, agriculture, and tourism.